Meningkatkan Berfikir Kritis Siswa Pada Materi Relasi dan Fungsi Menggunakan Model Problem Based Learning Di Kelas VIII SMP Negeri 2 Jeumpa - Rozanna, Nita (Postulat : Jurnal Inovasi Pendidikan Matematika, 2021)
This study aims to improve students' critical thinking skills in relation and function material using the Problem Based Learning learning model in class VIII SMP Negeri 2 Jeumpa. This type of research is Classroom Action Research. The subjects in this study were students of class VIII SMP Negeri 2 Jeumpa. The instruments in this study were teacher activity sheets, student activity sheets, and test questions. This research was conducted in three cycles, the first cycle consisting of one meeting, the second cycle consisting of one meeting, and the third cycle consisting of one meeting. Data collection techniques in this study are the results of tests and observations. Learning is carried out offline. The results of data processing in the first cycle showed that student learning outcomes were only 50% of students who completed learning, from the results of teacher observations, namely 3.00 which was classified as good, and from the results of student observations it was obtained that 72.22% were in good criteria. In the second cycle there was an increase, namely learning outcomes that reached 70% of students who completed learning, from the results of teacher observations, namely 3.27 which was classified as good, and from the results of student observations, it was obtained 80.56%. In the third cycle there was an increase again, namely the completeness of student learning outcomes as much as 90% which classically was included in the complete category, from the results of teacher observations, namely 3.60 which was classified as very good, and from the results of student observations it was obtained that 88.89% were at very good criteria. Based on the research results, it can be concluded that "Application of Problem Based Learning (PBL) Learning Model can Improve Students' Critical Thinking Ability on Relationship Materials and Functions of Class VIII SMP Negeri 2 Jeumpa".